Massive Pulmonary Embolism after a Short Episode of Physical Restraint in an Adolescent Psychiatric Patient - Leibold, Alexander; Melter, Michael; Doerfler, Christian; Alikadic, Samra; Zimmermann, Markus; Hanses, Frank; Zant, Robert (Journal of Pediatric Intensive Care, 2019)
Medical restraints, when used for short periods of time, can pose additional risk for deep vein thrombosis in adolescent psychiatric patients. The problem is often unrecognized, and there is a lack of awareness of this potential risk. However, as associated major adverse events may result in fatal outcomes, an individual patient's risk for deep vein thrombosis should be assessed and prophylactic anticoagulation may be indicated.
CRIS-Team WoS Importer:2019-11-15